THE EFFECT OF STRENGTH TRAINING USING RUBBER ROPES ON MOTOR BALANCE, SOME SERVICES, AND THE ACHIEVEMENT OF JAVELIN THROWING - Lecturer Ahmed Mohammed Kadhim Alzuwaini (Galaxy International Interdisciplinary Research Journal, 2023)
Therefore, functional strength exercises using rubber ropes according to the range of motion target all parts of the body, whether absolute or relative, and thus develop coordination and link between absolute and relative parts of the body and thus strengthen the muscles of the center, and based on this principle and through the experience of the researcher in teaching and training for the effectiveness of throwing The spear was found to have a slowdown in the movement between the parts of the body, as this was evident through the difficulty in the process of moving the body faster to the final stages of throwing, which led to the difficulty of controlling the correct motor performance in the final stages of the movement, and therefore the researcher used the experimental approach using the experimental design With one group appropriate to the nature of the research, as for the research sample, it was chosen by the researcher by the intentional method, and they are young javelin throwers, whose number is (6) players. A sample of (8) weeks and included (24) training units at a rate of (3) units per week. As for the conclusions of the research, all the exercises that were used to develop functional strength, whether for the muscles of the legs, trunk or arms, increased the efficiency of internal strength, and thus reflected positively on motor balance. Also, the use of functional strength training increased the effectiveness of achieving a good level of cohesion and motor coordination .